PENGARUH KEMANDIRIAN BELAJAR TERHADAP HASIL BELAJAR MATEMATIKA SISWA SMPN 1 BOJONEGARA PADA MATERI ALJABAR - Atika Indah Safitri; Heni Pujiastuti (Fakultas Keguruan dan Ilmu Pendidikan, 2020)
This study aims to recognize whether there is any influence between learning independence and mathematics learning outcomes of students of SMPN 1 Bojonegara on Algebra Material. This research is an ex post facto study, with a population of all students of SMPN 1 Bojonegara and for the sample taken classes VII C and VII D, totaling 75 people. Data collection is done by using a questionnaire for learning independence and tests for learning outcomes. The results of this study were obtained by processing data using SPSS version 26 to test the normality of learning independence data, learning outcomes and residues as well as to test linearity and significance of regression. The results showed that there was a significant influence between learning independence on learning outcomes with an influence of 96.03%